2020
DOI: 10.9734/arja/2020/v13i330107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tillage System and Cultivation Year on Secondary Metabolites and Antioxidant Capacity of Durum Wheat under Rainfed Conditions

Abstract: One of the proposed solutions to face climate change impact and to maintain food production sustainability is conservation agriculture. This study tries to determinate the effect of conventional tillage (CT) and no tillage (NT) on secondary metabolites such as total phenolics content (TPC), total flavonoids content (TFC) and antioxidants capacity (DPPH %) in relation to natural mycorrhization of durum wheat during the tillering stage for three cultivation years. The experiment was conducted in a referential fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
3
0
0
Order By: Relevance
“…These results are similar to those of Chaieb et al [40], Chaieb et al [44] who reported that under no tillage durum wheat and barley TPC at maturity stage and tillering stage did not show significant variability. Furthermore, Stake et al [45] foundd that management operations did not alter wheat phytochemicals concentrations.…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 92%
See 1 more Smart Citation
“…These results are similar to those of Chaieb et al [40], Chaieb et al [44] who reported that under no tillage durum wheat and barley TPC at maturity stage and tillering stage did not show significant variability. Furthermore, Stake et al [45] foundd that management operations did not alter wheat phytochemicals concentrations.…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 92%
“…Thus, analysis of variance of TFC showed that the effect of tillage is no significant. These results are similar to those of Chaieb et al [40] and Chaieb et al [44] who found that tillage system did not affect significantly durum wheat and barley TFC at maturity satge and tillering stage as affected. As well, Stracke et al [45] reported that mangement operations did not affect wheat phytochemicals concentrations.…”
Section: Total Flavonoids Content (Tfc)supporting
confidence: 92%
“…These results are in accoradance with those of Chaieb et al [32] and Chaieb et al [36] who studied durum wheat TPC respectively at maturity satge and tillering stage as affected by tillage systems and found that no significant effects were noted. In similar, Stake et al [37] recorded that mangement operations did not influence wheat phytochemicals concentrations.…”
Section: Total Phenolic Content (Tpc)supporting
confidence: 88%